Pengaruh Balance Scorecard Terhadap Sistem Pengukuran Kinerja Pada PT Rubberhocklie Medan - Parlindungan, Herison; Sari, Warsani Purnama (Mahesa Research Center, 2025)
This study aims to determine the effect of Balance Scorecard on the performance of PT. Rubber Hock Lie. The financial statements used in this study are balance sheet and income statement for 10 years (quarterly). There is 1 indicator for each perspective. Data processing using Spss version 26. The results obtained are a financial perspective, a consumer perspective and a internal business process perspective that positively affect PT Rubber Hock Lie company performance. However, the results show that the growth and learning perspective negatively affects PT Rubber Hock Lie company performance. The benefit of this research for science is that the use of each assessment perspective in balance scorecard analysis cannot be separated from each other so that cooperation between several fields of science is needed in the implementation of research.